(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY While studies show that antibiotic treatment for uncomplicated diverticulitis seems to have no benefit, most experts advocate antimicrobial therapy for complicated diverticulitis. However, even for uncomplicated diverticulitis, most clinicians are very reluctant to withhold antibiotics. Biomarkers could help to guide antibiotic therapy as this approach has been shown to be effective for acute respiratory infections. In this diagnostic cohort study we evaluated whether procalcitonin could be a biomarker to distinguish complicated from uncomplicated cases of diverticulitis. METHODS Complicated diverticulitis was defined as having abscess formation or perforation diagnosed by abdominal computed tomography (CT) scan. In all patients with suspected diverticulitis, procalcitonin values were measured at admission and on day 2. These values were blinded for clinicians, and treatment was carried out according to the physician’s judgement. Two groups (complicated vs uncomplicated diverticulitis) were defined. Patients who had received antibiotic treatment before admission were excluded. Difference in procalcitonin values was calculated for both groups using the Mann-Whitney test. Receiver operating characteristics (ROC) were calculated to determine cut-off values for procalcitonin according to the gold standard (abdominal CT scans). RESULTS 115 patients were included for analysis. 35 patients (30%) suffered from complicated diverticulitis. The median procalcitonin value for uncomplicated diverticulitis was significantly lower compared to complicated diverticulitis (median 0.05, interquartile range [IQR] 0.05–0.06 µg/l vs median 0.13, IQR 0.05–0.23 µg/l; p <0.0001). In the ROC analysis, the sensitivity and specificity were 81% and 91% when the highest procalcitonin value (days 1 and 2) was considered, with a cut-off value of 0.1 µg/l. CONCLUSION Procalcitonin was able to differentiate with a high sensitivity and specificity between complicated and uncomplicated cases of diverticulitis when combined with abdominal CT scans. As most clinicians still treat uncomplicated diverticulitis with antibiotics, procalcitonin could be an interesting parameter for guiding therapy and decreasing antibiotic usage. This should be further evaluated in randomised trials.